(untitled) (Cadernos de Psicologia Social do Trabalho, 2010)
This study investigated the emotions attributed to supervisors and employees involved in a work interaction in three different countries This research is based on Kemper's social interactional theory of emotions and the Algoe, Buswell and DeLamaters' studies. 238 people participated in this study: 100 were from Spain, 38 from England and 100 were from Brazil. From the total, 73 were male and 158 female (7 did not respond). The goal was to investigate whether the emotions attributed to supervisors and employees are influenced by information of professional status (employee or supervisor) and actor's sex (male or female). Also, whether the emotions attributed varied according to country and work experience. Four experimental conditions were created, they varied in sex and professional status. Previous studies concluded that professional status has more impact than sex on the attribution of emotions in the work place. The results of this study indicate that interaction at work is perceived as harmonious by participants from all three countries. However, positive emotions were attributed to supervisors more frequently - that shows the importance of professional status. Women attributed more negative emotions than men. The facial expression of sadness was the most chosen for employees and supervisors, although in this last case it was interpreted as expression of seriousness and emotional detachment.